Drought responses, phenotypic plasticity and survival of Mediterranean species in two different microclimatic sites. (1st February 2017) - Bongers, F. J.; Olmo, M.; Lopez‐Iglesias, B.; Anten, N. P. R.; Villar, R.
Abstract: Climate models predict a further drying of the Mediterranean summer. One way for plant species to persist during such climate changes is through acclimation. Here, we determine the extent to which trait plasticity in response to drought differs between species and between sites, and address the question whether there is a trade‐off between drought survival and phenotypic plasticity. Throughout the summer we measured physiological traits (photosynthesis – A max, stomatal conductance – g s, transpiration – E, leaf water potential – ψl) and structural traits (specific leaf area – SLA, leaf density – LD, leaf dry matter content – LDMC, leaf relative water content – LRWC) of leaves of eight woody species in two sites with slightly different microclimate (north‐ versus south‐facing slopes) in southern Spain. Plant recovery and survival was estimated after the summer drought period. We found high trait variability between species. In most variables, phenotypic plasticity was lower in the drier site. Phenotypic plasticity of SLA and LDMC correlated negatively with drought survival, which suggests a trade‐off between them. On the other hand, high phenotypic plasticity of SLA and LDMC was positively related to traits associated with rapid recovery and growth after the drought period. Although phenotypic plasticity is generally seen as favourable during stress conditions, here it seemed beneficial for favourable conditions. We propose that in environments with fluctuating drought periods there can be a trade‐off between drought survival and growth during favourable conditions. When climate become drier, species with high drought survival but low phenotypic plasticity might be selected for.